Efficacy of a referral center for patient-centered care in multiple myeloma: a cohort study. Issue 1 (June 2015) - Saccilotto, Indara; Bittencourt, Rosane; Fischer, Camila; Quevedo, Amanda; Hirakata, Vania; Picon, Paulo
Abstract Background Within the Brazilian Unified Health System (SUS), Referral Centers (RCs) are care facilities that provide specialized services. The objective of this study was to evaluate the efficacy of care provided to patients with multiple myeloma (MM) at a specialized RC (Hospital de Clínicas de Porto Alegre Referral Center for Multiple Myeloma, CRMM-HCPA) and to compare quality of life between patients with MM treated at CRMM-HCPA and those treated at non-RC facilities. Methods A 6-month cohort study was conducted in patients with MM receiving thalidomide from the Rio Grande do Sul State Health Department and treated at CRMM-HCPA and patients receiving treatment at other, non-RC care facilities. Thirty-two patients were included in the study, 19 from CRMM-HCPA and 13 from other institutions. To analyze the efficacy of care provided at CRMM-HCPA, the main outcome measure was the time from diagnosis to referral for autologous hematopoietic stem cell transplantation (HSCT). This outcome measure was assessed using questionnaires specifically designed for this study. Quality of life was also assessed, using the SF-36 questionnaire. Results Time from MM diagnosis to referral for autologous HSCT in each group was measured only in patients aged ≤ 65 years (n  = 25); of these, 15 were recruited from CRMM-HCPA and 10 from other institutions. In this analysis, there was a significant difference (p  = 0.036) in time elapsed between diagnosis and referral for autologous HSCT, which was significantly shorter for patients treated at CRMM-HCPA (median, 9 months; IQR, 8.5–14.5) than for those treated elsewhere (median, 24 months; IQR, 16–24). On quality of life analysis, there was a significant difference in the Social Functioning domain of the SF-36 questionnaire, which relates to performance of social activities (p  = 0.02). Conclusions The Referral Center model provided seems to be a more efficient treatment strategy as compared with other health care facilities, as it enabled a reduction in time to transplantation. Patients treated at CRMM-HCPA demonstrated greater ease in performing social activities, with less interference from physical or emotional problems.